Pengaruh Payment Online System (POS) dan Denda Pajak Bumi dan Bangunan Perdesaan Perkotaan (PBB P-2) Terhadap Kontribusi Penerimaan Pendapatan Asli Daerah Di Kecamatan Bukit Kecil Kota Palembang - Ramadani, Suci; Syafitri, Lili; Meiriasari, Vhika (JURNAL ONLINE INSAN AKUNTAN, 2024)
This research aims to determine the effect of the Online Payment System and Urban Rural Land and Building Tax Fines (PBB P-2) on the contribution of local income revenue in the Bukit Kecil sub-district, Palembang City. The method used in this research is quantitative. Data was collected based on questionnaire data and literature studies from the Regional Revenue Agency of Palembang City. The data obtained in this research came from 99 questionnaires filled out by taxpayers in Bukit Kecil District, Palembang. The data uses a Likert scale. The data analysis techniques used in this research include multiple linear regression analysis using classic assumption tests in the form of normality tests, heteroscedasticity tests, simultaneous significance tests and t tests and coefficient of determination tests using SPSS software. The results of this research show that the variables Online Payment System (X1) and Land and Urban Building Tax Fines (X2) have an influence on the Contribution of Regional Original Income Revenue (Y).   Keywords: Online Payment System, PBB Fines, Original Regional Income